Evaluating the emergence of elite professional golfers in europe with data envelopment analysis - Alcaraz, J.; Pastor, J. T.; Pastor, D.; del Campo, F. (European Journal of Human Movement, 2019)
The national golf organizations support the development of golf in their country and one of the signs of their success is the generation of elite professional golfers. In this paper, we analyze the emergence of elite professional golfers in eighteen European nations. The efficiency of these nations is measured through output-oriented Data Envelopment Analysis models. In particular, we propose variable and constant returns to scale radial models. The main purpose is to classify each of the nations as efficient or inefficient according to its ability to produce elite professional players and with regard to the inefficient ones, determine how far they have to go to achieve efficiency. We further propose a stepwise procedure for each inefficient nation that identifies a path towards the frontier with several intermediate points. The analysis of the results can be used by the nations for designing new strategies in order to improve their performance